Caesarean scar endometriosis - Kumari, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Endometriosis is defined by the presence and growth of ectopic functional endometrial tissue outside the uterus. The symptoms are nonspecific, typically involving abdominal wall pain at the time of menstruation. It commonly follows obstetrical and gynecological surgeries. The diagnosis is frequently made only after excision of scar the diseased tissue. A case report of 34 year old female patient presenting with scar endometriosis 7 years after her last LSCS (lower segment caesarean section). The patient came with the complaint of supra pubic swelling since 6 months, which was growing slowly. Her menstrual history was regular, but she had lower abdominal pain during menstruation. On clinical history, examination and USG finding the swelling was diagnosed as scar endometriosis.